The IPO decision : why and how companies go public - Draho, Jason, 1971- (Cheltenham, UK : Northampton, Mass. : Edward Elgar Publishing, 2004)
This title provides a comprehensive examination of the economic issues pertaining to the creation of new public companies placing the initial public offerings (IPOs) event within the larger context of the entire 'going-public process' for the company.
Includes bibliographical references (p. 344-375) and index.
oif 19/03/15
Loan
Keywords: Going public (Securities)